An Analysis of Grammatical and Lexical Errors in Nadiem Makarim's Speech - Theresia Christine Purba (Merwin Publisher, 2024)
The aims of the study were to (1) find out grammatical error in Speech Nadiem Makarim, Education Minister of Indonesia at Education World Forum (EWF), (2) To find out lexical error found by Speech Nadiem Makarim, Education Minister of Indonesia at Education World Forum (EWF). This method of presentation used qualitative and quantitative research. The data took from you tube channel. The data collected were analyzed each sentences. The findings of the study indicated that there was error in grammatical and lexical error in speech Nadiem Makariem. It could be seen from the data that omission have (48 % of 100%), addition have (15% of 100%), misformation (30% of 100%) and misodering (7% of 100%) in grammatical and lexical error, there was interlingual (59% of 100%) and intralingua (41% of 100%). There was differences value in grammatical and lexical error in the speech. The most error in the speech in omission with 22 errors.